Reaksi Pasar Terhadap China's Black Monday di Bursa Efek Indonesia - Satria, Gde Agung; Artini, Luh Gede Sri; Rahyuda, Henny (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.07.TAHUN 2017, 2017)
This study aimed to test market’s reaction of the China's Black Monday (CBM) at the Indonesian Stock Exchange (BEI). This research was conducted on all companies listed on the Stock Exchange which did not conduct corporate action in the event period. All the companies researched are divided into nine sectors and industries are classified according to the classification established by BEI called JASICA (Jakarta Industrial Classification). Event study method used to test the market reaction to the CBM. Based on the research results, there is a significant market reaction on eight sectoral index in the Indonesia Stock Exchange, namely the Agricultural Sector; Miscellaneous Industry; Basic Industry and Chemistry; Consumer Goods industry; Property and Real Estate; Transportation and Infrastructure; Finance; and Trade, Services and Investment while the Mining Sector Index does not react to CBM.
Keywords: abnormal return, china’s black monday, event study